(untitled) (Pandecta Research Law Journal, 2026)
The initiation of establishing a cultural infrastructure in the form of a Maritime Museum by the Semarang City Government manifests a strategic step in optimizing coastal geographic characteristics as an epicenter of maritime education, integrated tourism, and preservation of collective maritime memory. However, this ambitious project with an estimated building site area of ​​five hectares in the northern coastal region faces overlapping spatial regulations, uncertainty of land tenure status, and vulnerability of coastal ecosystem degradation. This study comprehensively analyzes the legal feasibility of land tenure, spatial planning, and environmental management across three alternative locations (Pearl of Java City, Polder Banger, and Tambachlorok). Utilizing a normative-juridical approach, this study evaluates the dynamics of foundational licensing post-implementation of the job creation regulations, which shifts the paradigm from traditional administrative permits to risk-based approvals. The comparative analysis recommends Pearl of Java City as the primary priority for construction based on spatial conformity parameters, subject to the mandatory completion of land rights transfer of reclaimed land as a municipal asset (Regional Property). This study concludes that the acquisition of hierarchically structured legal instruments ranging from land rights procurement, marine and terrestrial spatial conformity, to national institutional registration is an absolute prerequisite to ensure the sustainability of public investment, mitigation of administrative litigation risks, and ecological protection of the Semarang City coast.